Opozycyjnie o polskich mediach publicznych. Analiza publicystyki Jacka Żakowskiego (2005-2010) - Jędrzejczak, Paweł (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
According to Jacek Żakowski, politicization is the main barrier for the proper functioning of the public media in Poland. This paper discusses his point of view as far as the reasons of its condition and its meaning in a democratic state is concerned. J. Żakowski’s vision may be defined as an example of a civil opposition, because in his commentary he took a stand of an independent expert, who criticizes inappropriate relations between politicians and broadcasters and presents ideas for reforming the politicized media in Poland.